Real-life data for first-line combination immune-checkpoint inhibition and targeted therapy in patients with melanoma brain metastases. (October 2021) - Hilbers, Marie-Luise; Dimitriou, Florentia; Lau, Peter; Bhave, Prachi; McArthur, Grant A.; Zimmer, Lisa; Kudura, Ken; Gérard, Camille L.; Levesque, Mitchell P.; Michielin, Olivier; Dummer, Reinhard; Cheng, Phil F.; et al.
Abstract: Background: Melanoma brain metastases (MBM) have a poor prognosis. Systemic treatments that have improved outcomes in advanced melanoma have been shown to have an intracranial (IC) effect. We studied the efficacy and outcomes of combined immune checkpoint inhibitor ipilimumab/nivolumab (Combi-ICI) or targeted therapy (Combi-TT) as first-line treatment in MBM. Methods: MBM patients treated with Combi-ICI or Combi-TT within 3 months after MBM diagnosis. Endpoints were progression-free survival (PFS) and overall survival (OS). Results: 53 patients received Combi-ICI, 32% had symptomatic MBM and 33.9% elevated LDH. 71.7% required local treatment. The disease control rate was 60.3%. IC response rate (RR) was 43.8% at 3-months with durable responses at 6- (46.5%) and 12-months (53.1%). Extracranial (EC) RR was 44.7% at 3-months and 50% at 12-months. Median PFS was 9.6 months (95% CI 3.6-NR) and median overall survival (mOS) 44.8 months (95% CI; 26.2-NR). 63 patients received Combi-TT, 55.6% of patients had symptomatic MBM, 57.2% of patients had elevated LDH and 68.3% of patients required local treatment. The disease control rate was 60.4%. ICRR was 50% at 3-months, but dropped at 6-months (20.9%). ECRR was 69.2% at 3-months and 17.6% at 12-months. Median PFS was 5.8 months (95% CI 4.2–7.6) and mOS 14.2 months (95% CI 8.99–26.8). In BRAFV600 patients, 26.7% of patients received Combi-ICI and 73.3% Combi-TT with OS (p = 0.0053) and mPFS (p = 0.03) in favour to Combi-ICI. Conclusion: Combi-ICI showed prolonged mOS with sustainable IC and EC responses. Despite the initially increased efficacy, Combi-TT responses at 12 months were low. Combi-ICI appeared superior to Combi-TT for OS and PFS in BRAFV600 patients. Other clinical factors are determinants for first-line treatment choice. Highlights: Anti-PD1/anti-CTLA4 showed sustainable responses in melanoma brain metastases. Initial high intracranial and extracranial responses in BRAF/MEK were shortlived. Anti-PD1/anti-CTLA4 superseded targeted therapy in BRAF mutant patients. Local and systemic treatment was effective in patients with poor prognostic factors. Multiple intracranial and extracranial sites decreased efficacy in BRAF/MEK.